2017
DOI: 10.1002/mp.12062
|View full text |Cite
|
Sign up to set email alerts
|

A novel physical anthropomorphic breast phantom for 2D and 3D x‐ray imaging

Abstract: Purpose: Physical phantoms are central to the evaluation of 2D and 3D breast-imaging systems. Currently, available physical phantoms have limitations including unrealistic uniform background structure, large expense, or excessive fabrication time. The purpose of this work is to outline a method for rapidly creating realistic, inexpensive physical anthropomorphic phantoms for use in fullfield digital mammography (FFDM) and digital breast tomosynthesis (DBT). Methods: The phantom was first modeled using analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 26 publications
2
65
0
Order By: Relevance
“…More recently, Ikejimba et al (2017) reported a method for the creation of realistic, inexpensive physical anthropomorphic phantoms dedicated to use in full field digital mammography and digital breast tomosynthesis. The method is based on a virtual model, materialised in a slice-by-slice process through inkjet printing, using parchment paper and a radiopaque ink containing 33% (I 33% ) or 25% (I 25% ) iohexol by volume.…”
Section: Danail Ivanovmentioning
confidence: 99%
“…More recently, Ikejimba et al (2017) reported a method for the creation of realistic, inexpensive physical anthropomorphic phantoms dedicated to use in full field digital mammography and digital breast tomosynthesis. The method is based on a virtual model, materialised in a slice-by-slice process through inkjet printing, using parchment paper and a radiopaque ink containing 33% (I 33% ) or 25% (I 25% ) iohexol by volume.…”
Section: Danail Ivanovmentioning
confidence: 99%
“…A previous study using spectral analysis with a high‐purity Germanium photon counting detector showed that the linear attenuation coefficients of these materials were close to their reference values (see Fig. from Ikejimba et al). This study also showed that parchment paper from different companies had different characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This phantom, fabricated from a patient breast CT scan, was unique but had had a minor drawback in terms of resolution and material realism. Our group has recently developed a novel approach that uses inkjet printing to rapidly fabricate a physical phantom based on a virtual model . When signals are included, this phantom can be utilized as part of a method for task‐based evaluation of mammography systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, current image quality control (QC) procedures are mainly focused on the unprocessed — “for processing” — images, and do not evaluate these processed — “for presentation” — images. To allow for the evaluation of the “for presentation” images, which may involve nonlinear processes which depend on breast structure, during QC and assessment of the image processing, a transition toward anthropomorphic breast phantoms needs to be made …”
Section: Introductionmentioning
confidence: 99%